Smart leaders, smarter teams : how you and your team get unstuck to get results - Schwarz, Roger M., 1956- (Jossey-Bass, A Wiley Imprint, 2013)
This book provides practical guidance to help teams increase decision quality, decrease implementation time, foster innovation, get commitment, reduce costs, and increase trust.